Design and Implementation of an Electronic Identification Card - J. Flores-Escalante (Journal of Applied Research and Technology, 2009)
In this paper we present an "Electronic Identification Card" (EIC). This EIC is designed to provide a high degree of security for user authentication using biometrics, cryptography and steganography. The EIC encrypts the user's personal information as well as his fingerprint and then embed it in a photograph of the user's face. Two factors of authentication are used in the process: "something the user knows" and "something the user has", in order to provide layers of security to shield the card. The EIC gives the flexibility to operate in database systems, storage media like chips for smart cards or digital passports. We also developed schemes to authenticate users through the EIC, like remote authentication by a Web interface and the authentication in a local machine.